Imbalan Jasa Lingkungan untuk Pengentasan Kemiskinan - S. Suyanto; Noviana Khususiyah (Jurnal Agro Ekonomi, 2006)
EnglishThis study indicates that land right delivered to poor farmers as one type of reward for environmental services is not only important as income sources but also necessary to improve equity in income and land holding size. This study supports policy to hand over land right to poor farmers who provide environmental services and considers such initiative in favor of poor people under the state land management. Land right award for upland poor farmer is a win-win solution in respect to the interest of forest conservation and poverty alleviation. Reward mechanism for environmental services is not widely applied in Indonesia, although similar initiatives have been carried out at lower levels.IndonesianPenelitian ini menunjukan bahwa pemberian imbalan jasa lingkungan berupa hak kelola atas lahan (land right) kepada para petani miskin tidak hanya akan mengurangi kemiskinan tetapi juga akan meningkatkan pemerataan pendapatan dan penguasaan lahan. Hasil penelitian ini mendukung kebijakan pemberian imbalan jasa lingkungan bagi petani miskin sebagai kebijakan yang berpihak pada masyarakat miskin. Selain itu pemberian imbalan jasa lingkungan kepada petani miskin juga merupakan win-win solution antara kepentingan konservasi hutan dan peningkatan kesejahteraan petani miskin di sekitar hutan. Walapun di Indonesia mekanisme pembayaran jasa lingkungan belum berkembang dengan baik, namun telah banyak dilakukan inisiatif-inisiatif dalam skala kecil.